Heme oxygenase-1 plays a crucial role in chemoresistance in acute myeloid leukemia. Issue 7 (August 2015) - Zhe, Nana; Wang, Jishi; Chen, Shuya; Lin, Xiaojing; Chai, Qixiang; Zhang, Yaming; Zhao, Jiangyuan; Fang, Qing
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives The heme oxygenase-1 (HO-1) gene may contribute to the development of acquired chemoresistance in solid tumor cells, but its function in acute myeloid leukemia (AML) remains unclear. Therefore, we investigated whether the expressions of HO-1 mRNA and protein were associated with AML chemoresistance. Methods Bone marrow or peripheral blood was obtained from newly diagnosed (n = 26), relapsed (n = 10), and completely remitted (n = 18) patients with AML (M3 exclusion) and healthy donors (n = 10). Small interfering RNA was used to stably silence HO-1 gene expression in AML cell lines. The expressions of HO-1, hypoxia inducible factor-1ɑ (HIF-1ɑ), glucose transporter-1 (GLUT1) mRNA and proteins were measured by quantitative real-time PCR and Western blot. Cell viability was determined by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Apoptosis induction was analyzed by flow cytometry. Results The drug-resistant AML cell line HL-60R was significantly less sensitive to cytarabine and daunorubicin than HL-60 cells. HO-1 mRNA and proteins were highly expressed in HL-60R cells. However, down-regulating HO-1 significantly enhanced the sensitivity of HL-60R to chemotherapy, and the expressions of HIF-1ɑ and GLUT1 mRNA and proteins decreased. Meanwhile, the expressions of caspase-3 and caspase-8 proteins increased, while that of bcl-2 decreased. Overexpressions of HO-1, HIF-1ɑ, and GLUT1 were associated with poor response of AML to chemotherapy. Conclusions Overexpressions of HO-1, HIF-1ɑ, and GLUT1 might be involved in the chemoresistance of AML. HO-1 is a potential target to overcome the drug resistance of AML.